A case study on a misdiagnosis of ADHD - Castañeda Fernández, Jonathan; Fraga Varela, Tatiana (Pulso. Revista de educación, 2023)
Currently, Attention Deficit Hyperactivity Disorder (ADHD) is one of the most diagnosed mental conditions in childhood, at the same time it is one of the disorders that arouses the most attention and concern with in society. Given the high number of cases, a starting question arises: Is it possible that some of the individuals identified as having ADHD are misdiagnosed? Faced with this question, we are going to focus on a specific case, in which a series of indicators contradicted the initial diagnosis of hyperactivity. For this, the cognitive, social and creative skills of the subject have been re-evaluated through an explanatory, analytical, mixed research methodology (quantitative -BAS II, RIAS, BRIEF-2, CREA- and qualitative -observation, interviews and Torrance Test-), participatory, preordered and comparative. The final conclusion confirms the original hypothesis: the child has been misdiagnosted with ADHD. So this change in diagnosis implies a substantial change in the manner of treatment and intervention with the subject, both from an educational, social and family point of view.
Keywords: Attention Deficit Hyperactivity Disorder (ADHD); Misdiagnosis; Re-evaluation; High capacities